THE TOTAL WHITE CELL COUNT OF THE BLOOD AS AN INDICATOR OF ACUTE RADIATION DAMAGE AND ITS VALUE DURING THE FIRST FEW HOURS AFTER EXPOSURE. Issue 1 (January 1960) - Hulse, E. V.
Abstract : The total white cell count of the blood is of no value in assessing the degree of acute radiation damage in rats during the first 48 hours after exposure. This is because there is a transient neutrophilia after irradiation which counteracts, to a varying extent, the reduction in numbers of the other white cells. A similar neutrophilia occurs in human patients and there is no reason to expect that the total white cell count over the same period would be of any greater value in man. It is suggested, therefore, that the total white cell count of the blood is not suitable as a method for sorting radiation casualties.